Analytical assessment of 5.05 kWp grid tied photovoltaic plant performance on the system level in a composite climate of western India. (15th September 2016) - Dobaria, Bhaveshkumar; Pandya, Mahesh; Aware, Mohan
Abstract: The analytical assessment of 5.05 kWp grid tied photovoltaic plant performance on the system level has been carried out in this study. The solar PV plant has been installed on the roof of the block-A of the Darshan Institute of Engineering and Technology, Rajkot. India. The Darshan Institute of Engineering and Technology has been monitoring and recording all the parameters of 5.05 kWp grid tied solar PV power plant for 3 years. This paper helps in study of the performance and consistency of this system. The final yield, reference yield and performance ratio are observed to vary from 2.96 h/d to 5.43 h/d, 4.22 h/d to 7.29 h/d and 68%–83% respectively. The global in-plane solar radiation at the city of Rajkot is 2212 kWh/m 2 /annum. The average annual measured energy yield of the plant is found to be 1636 kWh/kWp. The total estimated system losses due to irradiance angle, temperature, module quality, array and cell mismatch, AC/DC wiring, MPPT, soiling and dirt, and inverter are found to be 26%. As a whole, the location, soiling pattern, design of PV and maintenance of solar PV system are the primary reasons of energy variability and system energy production. Highlights: The variation of final yields were 5.43 h/d–2.96 h/d observed during the year. The annual average final yield was 4.49 h/d. The average performance ratio of 74% was observed during year.